Electronic payment systems' characteristics and accounting information systems effectiveness: the moderating impact of perceived customers' uncertainty - Isam Saleh; Malik Abu Afifa; Abdallah Alkhawaja; Tamim Hannon (Cogent Business & Management, 2024)
This study investigates the impact of security, reliability, and assurance characteristics of electronic payment service systems on the effectiveness of accounting information systems (AIS) in Jordanian governmental institutions. Additionally, it examines the moderated effect of perceived customers' uncertainty in this context. Data for this study were collected through a questionnaire distributed to employees working in the accounting and financial departments of Jordanian governmental institutions that utilize AIS. A total of 213 questionnaires were randomly distributed to a sample, resulting in the retrieval of 128 questionnaires, yielding a recovery rate of 60%. All retrieved questionnaires were deemed valid for statistical analysis. The results statistically confirm a significant effect of security, reliability, and assurance on the effectiveness of AIS. Furthermore, they indicate that perceived customers' uncertainty does not moderate the relationship between security and the effectiveness of AIS. This study contributes to enhancing the effectiveness of financial data, which benefits decision-makers, policymakers, thought leaders, and development prospects. Additionally, it underscores the potential impact on the efficiency of AIS, which influences both the foundational and promotional aspects of financial data as well as the accuracy of accounting data.
Keywords: M41; M42; M48; 650; Electronic payment characteristics; accounting information system; perceived customers' uncertainty; governmental institutions; emerging economics